2006
DOI: 10.1007/s00277-005-0060-6
|View full text |Cite
|
Sign up to set email alerts
|

Improved therapeutic outcomes of DLBCL after introduction of rituximab in Korean patients

Abstract: With improvements in medical care and the resultant positive impact on life expectancy over the past few decades, the proportion of the population aged .65 years has seen significant increase, with the very elderly (age .80 years) expressed as a percentage of those aged .65 years almost doubling since 1950 (13.3% in 1950 increasing to 25.3% in 2015). 1 Like most cancers, the probability of acquiring non-Hodgkin lymphoma (NHL) increases with age (0.2% to 0.3% in those aged ,50 years and 1.4% to 1.8% in those ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The results from European Groupe D'Estude des Lymphomes des L'Adulte LNH-98-5 study (GELA) study demonstrated that 5 year overall survival (OS) is significantly higher in elderly patients with rituximab combination chemotherapy (Coiffer et al, 2002). In younger patients who had R-CHOP like chemotherapy had an increased 3-year event-free survival and OS compared to those without rituximab; 79% vs 59% and 93% vs 84% respectively (Pfreundschuh et al, 2006) More recently, the Asia groups including the Japanese, Korean, Chinese and Singaporean had also confirmed similar findings in patients with DLBCL (Park et al, 2006;Li et al, 2007;Ngo et al, 2008;Nishimori et al, 2009;Seiki et al, 2010). However, within the Asian countries, there are many which have limited health care resources in treating patients with lymphoma.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The results from European Groupe D'Estude des Lymphomes des L'Adulte LNH-98-5 study (GELA) study demonstrated that 5 year overall survival (OS) is significantly higher in elderly patients with rituximab combination chemotherapy (Coiffer et al, 2002). In younger patients who had R-CHOP like chemotherapy had an increased 3-year event-free survival and OS compared to those without rituximab; 79% vs 59% and 93% vs 84% respectively (Pfreundschuh et al, 2006) More recently, the Asia groups including the Japanese, Korean, Chinese and Singaporean had also confirmed similar findings in patients with DLBCL (Park et al, 2006;Li et al, 2007;Ngo et al, 2008;Nishimori et al, 2009;Seiki et al, 2010). However, within the Asian countries, there are many which have limited health care resources in treating patients with lymphoma.…”
Section: Introductionsupporting
confidence: 57%
“…R-CHOP or CHOP like chemotherapy has proven to improve overall survival of patients with aggressive NHL (Coiffer et al, 2002;Feugier et al, 2005;Sehn et al, 2005;Pfreundschuh et al, 2006). The results are indisputable and many studies done within Asia region had also proven so (Park et al, 2006;Li et al, 2007;Nishimori et al, 2009). A study which evaluated the outcomes of Western and Asian patients with DLBCL treated with R-CHOP found no difference in OS and progression free survival (PFS) (Castillo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To further examine the relationship between PELI1 expression and BCL6 expression in human cancer, PELI1 and BCL6 levels were assessed in 113 patients with DLBCLs classified according to World Health Organization guidelines (Figure 7). DLBCLs represent the most common form of non-Hodgkin lymphomas (NHLs) worldwide, accounting for approximately 40% of all new cases of lymphomas and 68% of all NHL cases among adult patients in Korea (13,22). In addition, BCL6 is known to facilitate lymphomagenesis of DLBCLs (12).…”
Section: Peli1 Expression Induces Constitutive Activation Of B Cell Smentioning
confidence: 99%
“…Park et al have reported an outcome benefit for 81 Korean patients treated with CHOP plus rituximab as compared to a historical cohort of 214 patients treated with the CHOP regimen [14]. Patients deemed palliative at diagnosis had been excluded from the analyses and the two studies have therefore been performed on selected patient populations.…”
Section: Discussionmentioning
confidence: 99%